Men standing at a battery of retorts. - Gordon, John C. (photographer):::Creator::::::::::::
Men standing next to retorts. Also called pressure canners or pressure cookers, retorts were used to cook and then cool canned fruit for purposes of sterilization. Chutes transport the cans from one vessel to the next in the cooking and cooling process.